Assessing the contribution of corporate social responsibility to the dynamics of sustainable markets: the role of corporate image, satisfaction, and customer loyalty - Cruz, Gimena; Fernández, Yover; Villar-Guevara, Miluska; Perez-Salluca, Mireya; Fernández-Mallma, Israel (Frontiers in Sustainability, 2026)
IntroductionCorporate social responsibility (CSR) has always played an essential role in the market, contributing to a more competitive and efficient business environment that must be incorporated across sectors, including financial institutions. This research examined whether CSR, customer satisfaction, and corporate image are related to customer loyalty.MethodsAn explanatory study was conducted with 424 Peruvians aged 18–68 (M = 32.70, SD = 10.66). Data were collected using a self-report scale of CSR, corporate image, satisfaction, and customer loyalty. The theoretical model was evaluated using the Partial Least Squares Structural Equation Modeling (PLS-SEM).ResultsA measurement model with adequate fit was obtained (α = 0.901–0.950; CR = 0.902–0.950; AVE = 0.746–0.910). Based on the results, a positive related was demonstrated between CSR with the customer loyalty (β = 0.264; p < 0.000; t = 4.593) and corporate image (β = 0.235; p < 0.000; t = 4.615); between satisfaction with the customer loyalty (β = 0.317; p < 0.000; t = 4.061) and corporate image (β = 0.645; p < 0.000; t = 12.766), and between corporate image with the customer loyalty (β = 0.235; p = 0.005; t = 2.810).DiscussionThe study offers a valuable theoretical contribution by situating the proposed model within the integrative framework of sustainability psychology, stakeholder theory, and the Triple Bottom Line (TBL). Furthermore, it provides a significant empirical contribution by arguing that strategic investments in CSR, such as environmental finance, digitalization, and inclusive initiatives, yield tangible environmental and social benefits. These practices align with the Sustainable Development Goals (SDGs) and strengthen customer loyalty. The findings encourage decision-makers to integrate measurable sustainability actions informed by sustainability psychology to understand the individual and collective psychological processes that promote sustainable practices across organizational, social, and environmental contexts.